Underrated primary biogenic origin and lifetime of atmospheric formic and acetic acid - Xinqing Lee (Nature Portfolio, 2021)
Abstract Formic and acetic acids are ubiquitous in the troposphere, playing an important role in the atmospheric chemistry. Recent model studies ended up with substantial low bias on their tropospheric budgets presumably due to a large missing biogenic source derived most likely from photochemical oxidation of long-lived volatile organic compound(s), i.e., a secondary biogenic emission. Here, by studying the stable carbon isotope composition of formic and acetic acid in couple in the troposphere and relevant sources, we find the gap relates to primary biogenic emission and atmospheric lifetime of the acids. We show the primary biogenic emission is only second to the secondary biogenic emission as a strong source. Marine emission is the least one yet present in all the tropospheric environments except some local air. Long-distance transport of this origin indicates the lifetime over 5 days for both acids. Our results indicate that recent simulations underrated both primary biogenic emission and the lifetime. These underestimations would inevitably bias low the modeled results, especially in the low and free troposphere where primary biogenic emission and lifetime has the most pronounced influence, respectively.